Welding Quality Control Using Seven Tools Method AT PT. XYZ - Hamzah, Mohammad; Donoriyanto , Dwi Sukma (The Indonesian Journal of Computer Science, 2024)
PT. XYZ is the largest shipyard company in Indonesia. In the ship production process, PT. XYZ Indonesia strives to provide the best for consumers, especially in terms of the quality of making the KCR-301 ship, where during the welding process there are still several defects such as Incomplete Penetration, Incomplete Fusion, Slag Inclusion and Porosity. The purpose of this study was to determine the percentage of the most dominant defects in welding and provide recommendations for improving the quality of welding on the KCR-301 ship using the seven tools method. Based on the results of the study, it was found that the most dominant defect in welding quality was Incomplete Penetration of 800 mm (2.93%), then followed by Incomplete Fusion defects of 630 mm (2.31%), Slag Inclusion defects of 595 mm (2.18%), and Porosity defects of 460 mm or (1.69%). The proposed improvements to the most dominant ones with the proposed recommendations for improvement are to emphasize to the welder to be required to better understand the procedures and SOPs that will be used to weld properly.